Carcass study in relation to weight and grading meat in alpacas (Vicugna pacos) - Quispe P., Edgar (2012)
This research was carried out in the Huancavelica slaughterhouse, located at 3680 meters above sea level. Data were collected from 200 Huacaya alpacas to characterize the carcasses in relation to body weight (BW), hot carcass weight (HCW), cold carcass weight (CCW) and grading meat. BW was 49.5 and 55.6 kg for males and females, and 51.3 and 53.1 kg for 4-tooth and full mouth animals respectively. HCW were 27.3 and 30.0 kg for males and females, and 28.1 and 28.8 kg for 4-tooth and alpaca full mouth respectively. CCW were 26.9 and 29.6 kg for males and females, and 27.7 and 28.4 kg for 4-tooth and alpaca full mouth respectively. Most carcasses were classified as second grade (38.0%) and industrial meat (36.5%) and none was of extra grade. Simple linear equations to predict HCW and CCW from BW showed coefficients of determination of 68.5 and 68.3% respectively. Moreover, highly significant positive correlations (p<0.01) were found between the variables under study with values over 0.8, yielding an almost perfect match between HCW and CCW.